AL-QUR’AN DITURUNKAN DALAM TUJUH HURUF - Hamnah Hamnah (CV. Adiba Aisha Amira, 2021)
The history of the development of Qirā'āt began at the time of the Prophet when the Qur'an was revealed in seven letters and continued from generation to generation to give birth to a branch of practical science, namely Qirā'āt Science. 'āt Mutawatir and Mashūr. The wisdom with the existence of various Qirā'āt is one form of the ease and flexibility of Islam for its people in worshiping and practicing the contents of its religious teachings. The various qira'at does not mean that the Qur'an has different readings which cause differences in content according to differences, but shows that the Qur'an is very rich in a variety of readings which is a greeting of its beauty..